-- Copyright (c) 2014 Microsoft Corporation. All rights reserved. -- Released under Apache 2.0 license as described in the file LICENSE. -- Author: Leonardo de Moura import logic.eq inductive acc {A : Type} (R : A → A → Prop) : A → Prop := intro : ∀x, (∀ y, R y x → acc R y) → acc R x namespace acc variables {A : Type} {R : A → A → Prop} definition inv {x y : A} (H₁ : acc R x) (H₂ : R y x) : acc R y := acc.rec_on H₁ (λ x₁ ac₁ iH H₂, ac₁ y H₂) H₂ end acc inductive well_founded [class] {A : Type} (R : A → A → Prop) : Prop := intro : (∀ a, acc R a) → well_founded R namespace well_founded definition apply [coercion] {A : Type} {R : A → A → Prop} (wf : well_founded R) : ∀a, acc R a := take a, well_founded.rec_on wf (λp, p) a context parameters {A : Type} {R : A → A → Prop} infix `≺`:50 := R hypothesis [Hwf : well_founded R] theorem recursion {C : A → Type} (a : A) (H : Πx, (Πy, y ≺ x → C y) → C x) : C a := acc.rec_on (Hwf a) (λ x₁ ac₁ iH, H x₁ iH) theorem indunction {C : A → Prop} (a : A) (H : ∀x, (∀y, y ≺ x → C y) → C x) : C a := recursion a H variable {C : A → Type} variable F : Πx, (Πy, y ≺ x → C y) → C x definition fix_F (x : A) (a : acc R x) : C x := acc.rec_on a (λ x₁ ac₁ iH, F x₁ iH) theorem fix_F_eq (x : A) (r : acc R x) : fix_F F x r = F x (λ (y : A) (p : y ≺ x), fix_F F y (acc.inv r p)) := have gen : Π r : acc R x, fix_F F x r = F x (λ (y : A) (p : y ≺ x), fix_F F y (acc.inv r p)), from acc.rec_on r (λ x₁ ac iH (r₁ : acc R x₁), -- The proof is straightforward after we replace r₁ with acc.intro (to "unblock" evaluation). calc fix_F F x₁ r₁ = fix_F F x₁ (acc.intro x₁ ac) : proof_irrel r₁ ... = F x₁ (λ y ay, fix_F F y (acc.inv r₁ ay)) : rfl), gen r end variables {A : Type} {C : A → Type} {R : A → A → Prop} -- Well-founded fixpoint definition fix [Hwf : well_founded R] (F : Πx, (Πy, R y x → C y) → C x) (x : A) : C x := fix_F F x (Hwf x) -- Well-founded fixpoint satisfies fixpoint equation theorem fix_eq [Hwf : well_founded R] (F : Πx, (Πy, R y x → C y) → C x) (x : A) : fix F x = F x (λy h, fix F y) := calc -- The proof is straightforward, it just uses fix_F_eq and proof irrelevance fix F x = F x (λy h, fix_F F y (acc.inv (Hwf x) h)) : fix_F_eq F x (Hwf x) ... = F x (λy h, fix F y) : rfl -- proof irrelevance is used here end well_founded